Costly pollution abatement, competitiveness, and plant location decisions - James R. Markusen (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This quote contains two separate policy suggestions: (1) Trade barriers insulate production and welfare from any adverse responses to costly environmental restrictions. (2) Banning multinationals would insulate production and welfare from any adverse effects of costly environmental restrictions. This paper adapts an oligopoly model, in which multinationals (multi-plant firms) can arise endogenously, to examine this position. This paper finds that: (1) Trade barriers insulate production but not welfare from adverse effects of costly environmental restrictions. (2) Banning multinationals does not insulate production and welfare from any adverse effects of these restrictions or regulations. On the contrary, multinationals appear to smooth production effects, but this is because multinationals arise in equilibrium when trade costs are high. In addition, the paper finds that the form taken by cost increases is crucial: restrictions that fall on fixed costs (e.g., more efficient burners and motors) have much smaller effects on production and welfare than restrictions that fall on marginal costs (e.g., cleaner fuels).
Keywords: 330